Analysis of Genetic Data on Jewish Populations I. Historical Background, Demographic Features, and Genetic Markers - Bonne-Tamir, Batsheva; Karlin, Samuel; Kenett, Ron (American Journal of Human Genetics, 1979)
Part I describes the data sets on which the analysis of Part II is based. This covers the nature of the populations sampled, the extent to which the samples are representative, and a brief review of historical and demographic facts on the populations involved.
Keywords: Judaïsme -- Djerba

Deux rapports de Salomon Reinach sur les Juifs de Tunisie au début du protectorat - Attal, Robert (Revue des études juives, 1979)
Keywords: Judaïsme -- Djerba

The jews of Arab lands: a history and source book - Stillman, Norman A. (The jewish publication society, 1979)
Keywords: Judaïsme -- Djerba

Femmes et voisinages à Hara Kebira : rapport d’un stage effectué à Hara Kebira, dans l’île de Jerba - Reenen, Joke van (Groupe d’études Tunis, 1979)
Keywords: Judaïsme -- Djerba

Femmes et voisinages à Hara Kebira : rapport d'un stage effectué à Hara Kebira, dans l'île de Jerba - Joke van Reenen, Johanna Hendrika (Université Libre, 1979)
Keywords: Judaïsme -- Djerba